2013
DOI: 10.3390/molecules181113487
|View full text |Cite
|
Sign up to set email alerts
|

Template-Based de Novo Design for Type II Kinase Inhibitors and Its Extended Application to Acetylcholinesterase Inhibitors

Abstract: There is a compelling need to discover type II inhibitors targeting the unique DFG-out inactive kinase conformation since they are likely to possess greater potency and selectivity relative to traditional type I inhibitors. Using a known inhibitor, such as a currently available and approved drug or inhibitor, as a template to design new drugs via computational de novo design is helpful when working with known ligand-receptor interactions. This study proposes a new template-based de novo design protocol to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The molecular functions in the ovary revealed that the highest DEGs were recorded in “transferase phosphorus containing group” followed by “phosphotransferase activity alcohol group as acceptor.” It has been reported that transferase are highly essential in a wide range of physiological activities by catalyzing different biological processes that are important to a living system ( Fyte et al, 2012 ). Moreover, phosphotransferase, also known as phosphorus transferases is a large enzyme category among all transferases ( Su et al, 2013 ). The activities of transferase include but are not limited to essential metabolism, genetic regulations, and detoxification ( Fyte et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular functions in the ovary revealed that the highest DEGs were recorded in “transferase phosphorus containing group” followed by “phosphotransferase activity alcohol group as acceptor.” It has been reported that transferase are highly essential in a wide range of physiological activities by catalyzing different biological processes that are important to a living system ( Fyte et al, 2012 ). Moreover, phosphotransferase, also known as phosphorus transferases is a large enzyme category among all transferases ( Su et al, 2013 ). The activities of transferase include but are not limited to essential metabolism, genetic regulations, and detoxification ( Fyte et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computational chemistry plays an important role in the design of new drug-like molecules [1,2,3,4,5], catalysts [6,7,8], and novel solvents of ionic liquids [9,10,11]. De novo molecular design has been an active research area of drug design/discovery over the last decades, and many approaches such as LUDI [12], LEA3D [13], Flux [14,15], and pharmacophore-linked fragment virtual screening (PFVS) [16] have been developed by using protein and ligand structures.…”
Section: Introductionmentioning
confidence: 99%